Personality Traits and Occupational Interest: Basis for Career Guidance Program - B. Elnar, Ryan Dale (2014)
The current study devised an empirically-based career guidance program using standardized measures among 236 puposively sampled Filipino college freshmen (n=78 male, n=158 female). Bivariate analyses between 16 PF’s Global Factor Scales (GFS) and Occupational Aptitude Survey and Interest Schedule (OASIS-2 IS) reveal the association of students’ GFS dimensions on their Occupational Interests (OI): anxiety and accommodating; tough-mindedness and mechanical; and independence and leading-influencing. Multivariate analyses found some demographics which influenced students’ GFS and OI: self-control is affected by age; tough-mindedness is affected by sex; independence is affected by course; sex and course affects various OI dimensions (nature, protective, mechanical, industrial, business detail, accommodating, humanitarian, artistic, and selling). Expectantly, coefficient determination (R2 mean = 0.031 or 31%) arrived at a significant level for all GFS except extraversion as valid predictors of some dimensions of the OI. Theoretical and practical applications are discussed. Keywords: personality traits, occupational interest, career guidance progra